Pengaruh Quick Ratio, Long Term Debt Ratio dan Perputaran Modal Kerja Terhadap Rentabilitas Pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Nursidin, M. (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In a company, working capital is inseparable. Working capital is provided to directly finance the company's daily routine activities. Working capital has been circulating continuously since the company was founded and will end when the company is liquidated or dissolved. In determining working capital policies, it must be efficient, working capital that exceeds needs will also result in capital sedimentation so that indirectly it means that the company's profits are not optimally utilized, conversely working capital that is too little also results in the company's liquidity only being able to be done after comparing the profits that have been generated and the amount of capital invested in the company, therefore it is necessary to calculate profitability. A good economy will increase people's income so that demand for consumer goods will also increase and then increase the company's profits. Consumer Goods companies will also benefit from the level of sales. In this situation, investors will be interested in investing their capital in the company, so that it will influence the company to disclose its financial statements.